Secondary-Level and Professional Education For The JewishPeople in The Pale of Settlement and in Siberia in TheSecond Half of The Xixth-The Beginning of The Xxth Centuries - Shvagrukova E. V. Ekaterina Vasilevna (2016, 2016)
Title screen